2021
DOI: 10.1126/sciadv.abd1707
|View full text |Cite
|
Sign up to set email alerts
|

Human physiomimetic model integrating microphysiological systems of the gut, liver, and brain for studies of neurodegenerative diseases

Abstract: Slow progress in the fight against neurodegenerative diseases (NDs) motivates an urgent need for highly controlled in vitro systems to investigate organ-organ– and organ-immune–specific interactions relevant for disease pathophysiology. Of particular interest is the gut/microbiome-liver-brain axis for parsing out how genetic and environmental factors contribute to NDs. We have developed a mesofluidic platform technology to study gut-liver-cerebral interactions in the context of Parkinson’s disease (PD). It con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
76
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(88 citation statements)
references
References 96 publications
0
76
0
Order By: Relevance
“…Experimental results revealed that the fluidic circuit elements exhibited performance characteristics consistent with their electrical counterparts both independently and when integrated as part of larger integrated fluidic circuits. Although the fluidic circuits in this work were designed with respect to soft robots, it should be noted that fluidic valving and routing capabilities are widely used in chemical, biological, and biomedical fields (48), and thus, the fluidic processing approaches demonstrated here could be extended to support such applications.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental results revealed that the fluidic circuit elements exhibited performance characteristics consistent with their electrical counterparts both independently and when integrated as part of larger integrated fluidic circuits. Although the fluidic circuits in this work were designed with respect to soft robots, it should be noted that fluidic valving and routing capabilities are widely used in chemical, biological, and biomedical fields (48), and thus, the fluidic processing approaches demonstrated here could be extended to support such applications.…”
Section: Discussionmentioning
confidence: 99%
“…Novel, promising approaches including 2Phatal and the use of tri-cultures supporting neurons, microglia, and astrocytes may enable such opportunities, allowing multi-cellular interactions to be observed in vivo and in vitro (Goshi et al, 2020 ; Guttikonda et al, 2021 ). Furthermore, the recent development of an in vitro all-human physiomimetic model has exciting implications for how we understand neurodegenerative diseases, broadening the questions that can be asked about how microglia and astrocytes are impacted by or contribute to aging and disease (Trapecar et al, 2021 ). This model links three complex microphysiological systems including the gut/immune, liver/immune, and cerebral/immune systems in a common culture media containing circulating immune cells in continuous coculture (Trapecar et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the recent development of an in vitro all-human physiomimetic model has exciting implications for how we understand neurodegenerative diseases, broadening the questions that can be asked about how microglia and astrocytes are impacted by or contribute to aging and disease (Trapecar et al, 2021 ). This model links three complex microphysiological systems including the gut/immune, liver/immune, and cerebral/immune systems in a common culture media containing circulating immune cells in continuous coculture (Trapecar et al, 2021 ). Using an in vitro human physiomimetic model enables a controlled systems approach that will allow organ-organ and organ-immune system interactions mimicking in vivo like behavior to be explored.…”
Section: Discussionmentioning
confidence: 99%
“… 62 Recently, Trapecar et al used a multi-OoC system to demonstrate that systemic interaction between a Gut–Liver-Chip and a Brain-on-a-Chip enhances the features of in vivo -like behavior of cerebral micro-physiological system (MPS), and that microbiome-associated short-chain fatty acids increase the expression of pathways associated with Parkinson's disease pathology. 123 While there are some recent reviews of multi-OoC platforms (for example, Refs. 7 , 15 , 64–67 , and 124–127 ), this technology is rapidly developing, offering a significant promise, alongside many challenges to overcome.…”
Section: State Of the Artmentioning
confidence: 99%